The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1109/tvcg.2017.2656897
|View full text |Cite
|
Sign up to set email alerts
|

Memory-Efficient On-the-Fly Voxelization and Rendering of Particle Data

Abstract: In this paper we present a novel GPU-friendly real-time voxelization technique for rendering homogeneous media that is defined by particles, e.g., fluids obtained from particle-based simulations such as Smoothed Particle Hydrodynamics (SPH). Our method computes view-adaptive binary voxelizations with on-the-fly compression of a tiled perspective voxel grid, achieving higher resolutions than previous approaches. It allows for interactive generation of realistic images, enabling advanced rendering techniques suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…In order to make the results as comparable as possible we have to account for the three major factors affecting the rendering time: the number of points/particles in the scene, the screen resolution, and the number of spp. All methods use 1 spp except [53] and [47], which use 2 spp for particle inter-reflections and the methods' spp counts fairly compatible when assessing performance. We have categorized methods achieving real time (≥ 10FPS) or interactive real time (≥ 1FPS), mutually exclusively, and reported the closest maximum number of points still renderable in real-time or interactive frame rates.…”
Section: Summary and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In order to make the results as comparable as possible we have to account for the three major factors affecting the rendering time: the number of points/particles in the scene, the screen resolution, and the number of spp. All methods use 1 spp except [53] and [47], which use 2 spp for particle inter-reflections and the methods' spp counts fairly compatible when assessing performance. We have categorized methods achieving real time (≥ 10FPS) or interactive real time (≥ 1FPS), mutually exclusively, and reported the closest maximum number of points still renderable in real-time or interactive frame rates.…”
Section: Summary and Discussionmentioning
confidence: 96%
“…A full GPU implementation of a view aligned voxelized sphere particle structure showed that interparticle refractions and reflections with up to seven fluid layers was possible at interactive frame rates. A view space aligned voxelized sphere particle method fully implemented on the GPU was published in [53]. With photorealistic interparticle refractions and reflections between up to seven fluid layers, they achieved interactive frame rates.…”
Section: Real-time Particle-and Fluid-based Methodsmentioning
confidence: 99%
“…Zirr and Dachsbacher perform on‐the‐fly voxelization [ZD18] to interactively render photorealistic particle‐based fluids. Reichl et al .…”
Section: Related Workmentioning
confidence: 99%
“…Dos Santos Brito et al [dSBVeSTT18] presented a ray tracing method for particle data that achieves several frames per second for millions of particles. Zirr and Dachsbacher [ZD18] proposed an on‐the‐fly voxelization method for particle data as well as an accelerated ray casting approach for rendering that achieves a considerable speedup compared to the method by Fraedrich et al [FAW10]. While these approaches focus on more general particle data, several techniques specifically targeted at molecular visualization have been presented.…”
Section: Related Workmentioning
confidence: 99%